THE ROLE AND SIGNIFICANCE OF THE KI67 PROLIFERATION MARKER IN DIFFERENTIATED THYROID CARCINOMA (World Bulletin of Public Health, 2025)
This article presents data from literature sources regarding the epidemiology, diagnosis, and treatment methods of differentiated thyroid carcinoma. The Ki67 proliferation marker was evaluated in tissue samples from 20 patients with differentiated thyroid carcinoma. The results of the immunohistochemical analysis were assessed based on the intensity of the positive reaction — mild, moderate, and high. The study describes the percentage distribution of patients showing different levels of Ki67 expression
Keywords: Differentiated thyroid carcinoma; immunohistochemistry; Ki67; proliferative activity